The need and challenges for development of vaccines against emerging infectious diseases - Sue Ann Costa Clemens; Ralf Clemens (Elsevier, 2023)
Objective: To identify and describe learnings from past pandemics and to suggest a framework for vaccine development as part of epi/pandemic readiness. Source of data: Articles/ reviews/letters on pandemic preparedness/ vaccines published between 2005 and 2022 in PubMed, MEDLINE, MedRxiv, BioRxiv, Research Square, Gates Open Research; who.int, cepi.net, visualcapitalist.com, airfinity.com, ted.com websites; press releases. Summary of findings: Disease pandemics caused by emerging pathogens impacted the social development, health and wealth of most societies in human history. In an outbreak, the first months determine its course. To block an exponential spread and the development of an epi/ pandemic early, vaccine availability in sufficient quantities is of paramount importance. It is inevitable that new human viruses will emerge. Any future pandemic will come likely from RNA viruses through zoonotic or vector transmission, but we cannot predict when or where "Disease X" will strike. Public health, scientific and societal readiness plans need to include: continuous identification of new viruses in common mammalian reservoir hosts; continuous epidemiological surveillance, including wastewater sampling; establishment of prototype vaccine libraries against various virus families sharing functional and structural properties; testing of various and innovative vaccine platforms including mRNA, vector, nasal or oral vaccines for suitability by virus family; functional clinical trial sites and laboratory networks in various geographies; more efficient phasing of preclinical and clinical activities; global harmonization and streamlining of regulatory requirements including pre-established protocols; and societal preparedness including combating any pandemic of misinformation. Conclusions: "Outbreaks are unavoidable, pandemics are optional".